THE ROLE OF MASS SPORTS EVENTS IN THE POPULARIZATION OF THE GTO COMPLEX AND THE PREPARATION OF THE WORKING-CAPACITY POPULATION TO PERFORM THE TESTS OF THE VFSK GTO - Bobkova, E.N.; Zhukov, S.V.; Kireeva, A.V.; Zyurin, E.A.; Petruk, E.N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the role of mass sports events in the popularization of the GTO complex in the preparation of the able-bodied population for the performance of tests of the VFSK GTO. Methods and structure of the study. In the course of scientific work, an analysis was made of plans for sports events aimed at organizing mass propaganda campaigns to promote the All-Russian physical culture and sports complex "Ready for Labor and Defense" (VFSK GTO) of the Ministry of Sports of the Russian Federation for 2018-2021, analysis of data from the analytical media monitoring system "Medialogy", a survey was conducted (18 constituent entities of the Russian Federa- tion, 546 respondents of working age). Results and conclusions. In the course of scientific work, it was revealed that the involvement of workers in the process of fulfilling the GTO standards through participation in mass sports events should occur, first of all, at the place of work. A large role in the popularization of mass sports work, including the implementation of the GTO complex in labor collectives, is assigned to corporate media. As part of the search for a solution to the problems of increasing the effectiveness of physical culture and sports events among the adult population, it is necessary to take into account the personal interests of citizens, since society has formed an order for a comfortable and accessible physical culture and sports environment for practicing “sports”.